NIR light-triggered shrinkable thermoresponsive PNVCL nanoshells for cancer theranostics - Chauhan, Deepak S.; Singaravelu, Indulekha; Gottipalli, Rupesh; Reddy, B. Pradeep K.; Chikate, Tanmayee; Gupta, Ramkrishn; Jahagirdar, Dushyant N.; Prasad, Rajendra; De, Abhijit; Srivastava, Rohit (RSC Advances, 2017)
For the localized treatment of a tumor in a more controlled fashion, several stimuli-responsive nanocarriers and minimally or non-invasive techniques like photothermal therapy (PTT) have emerged. However, PTT is limited to only treatment of small and superficial tumors due to the inability of NIR light to penetrate more and kill the core cells of large and deep-seated tumors. As a preliminary step towards addressing the problem, NIR light-triggered thermoresponsive theranostic nanoshell consisting of chitosan-grafted poly(N-vinyl caprolactam) as core and biocompatible gold as shell (Au PNVCL NS) are synthesized and well characterized by various techniques. PNVCL is polymerized from N-vinyl caprolactam using free radical polymerization method, and chitosan is grafted to raise its lower critical solution temperature (LCST) to hyperthermic temperature (∼43 °C). Surface plasmon resonant gold shell over PNVCL NPs core is assembled by ascorbic acid-driven in situ reduction. Core to shell diameter ratio is controlled to tune the peak in NIR region (750 nm). Therapeutic potential of Au PNVCL NS is determined over breast cancer cells MCF-7, while diagnostic potential is compared with the commercial contrast agent-Omnipaque.